Tres lecciones sobre documentación general (sistemas de información y documentación) / José López Hernández, José López Yepes, JUan Ros García - López Yepes, JoséRos García, Juan; López Hernández, José
En: Cuadernos E.U.B.D. Complutense. Vol. 1, n. 2 (1991)